Prevalence and factors associated with menstruation-related school absenteeism among adolescent girls in rural northern Ghana - Kumbeni, Maxwell Tii (BMC Womens Health, 2021)
BACKGROUND: Although menstruation is a normal physiological process that begins in girls during adolescence, it has the potential to negatively impact on the self-esteem and education of girls particularly those from low- and middle-income countries. We investigated the prevalence and factors associated with menstruation-related school absenteeism among adolescent girls in the Talensi district of rural northern Ghana. METHODS: We conducted a cross-sectional survey among 705 adolescent girls aged 12–19 years who had attained menarche. The sample size was estimated using Epi Info version 6 at 95% confidence interval and a 5% margin of error. A two-stage sampling technique was employed to recruit participants. We conducted univariate and multivariate logistic regression models to determine factors associated with menstruation-related school absenteeism which was defined as “being absent from school due to menstruation-related issues during the last menstruation.” RESULTS: The prevalence of menstruation-related school absenteeism was 27.5%. School absenteeism ranged from one to seven days during the menstrual period. Older adolescent girls, (aOR = 2.38, 95% CI 1.29–4.40), use of cloth as a sanitary material at the last menstruation, (aOR = 3.21, 95% CI 2.22–4.63), and cultural restriction, (aOR = 2.54, 95% CI 1.76–3.67) were associated with higher odds of menstruation-related school absenteeism. Meanwhile, girls from moderate income parent(s), [aOR = 0.57 95% CI 0.34–0.94] had lower odds of menstruation-related school absenteeism. Mother’s education and privacy in school were only significant at the univariate level. CONCLUSIONS: The prevalence of menstruation-related school absenteeism highlights the need for interventions aimed at improving the availability of sanitary pads for girls, eliminating cultural restrictions associated with menstruation, and also improving parent(s) income level.